DETERMINATION AND COMPARISION OF NON ENZYMATIC ANTIOXIDANTS FROM DIFFERENT LOCAL VARIETIES OF BANANA (MUSA SP.) - POONGODI (International Journal of Pharma and Bio Sciences, 2012)
The present study mainly focused on quantification and comparison of non enzymatic antioxidants from pulp extracts of nine varieties of banana viz Kadali, Karpooravalli, Monthan, Nenthiran, Pachainadan, Poovan, Rasthali, Robusta and Sevvazhai. The non enzymatic antioxidants such as total reduced glutathione, vitamin A, vitamin C, vitamin E were quantified from banana pulp extract. The data obtained were subjected to statistical analysis and results were compared. All the banana varieties exhibited significant amount antioxidants. Rasthali,Poovan,karpooravalli Robusta showed highest amount of antioxidant enzymes compared to other varieties.